An audit of the quality of inpatient care for adults with learning disability in the UK. Issue 4 (18th April 2016) - Sheehan, Rory; Gandesha, Aarti; Hassiotis, Angela; Gallagher, Pamela; Burnell, Matthew; Jones, Glyn; Kerr, Michael; Hall, Ian; Chaplin, Robert; Crawford, Michael J
Abstract : Objectives: To audit patient hospital records to evaluate the performance of acute general and mental health services in delivering inpatient care to people with learning disability and explore the influence of organisational factors on the quality of care they deliver. Setting: Nine acute general hospital Trusts and six mental health services. Participants: Adults with learning disability who received inpatient hospital care between May 2013 and April 2014. Primary and secondary outcome measures: Data on seven key indicators of high-quality care were collected from 176 patients. These covered physical health/monitoring, communication and meeting needs, capacity and decision-making, discharge planning and carer involvement. The impact of services having an electronic system for flagging patients with learning disability and employing a learning disability liaison nurse was assessed. Results: Indicators of physical healthcare (body mass index, swallowing assessment, epilepsy risk assessment) were poorly recorded in acute general and mental health inpatient settings. Overall, only 34 (19.3%) patients received any assessment of swallowing and 12 of the 57 with epilepsy (21.1%) had an epilepsy risk assessment. For most quality indicators, there was a non-statistically significant trend for improved performance in services with a learning disability liaison nurse. The presence of an electronic flagging system showed less evidence of benefit. Conclusions: Inpatient care for people with learning disability needs to be improved. The work gives tentative support to the role of a learning disability liaison nurse in acute general and mental health services, but further work is needed to confirm these benefits and to trial other interventions that might improve the quality and safety of care for this high-need group.